2009
DOI: 10.1007/s10725-009-9388-6
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous ethylene in indirect somatic embryogenesis of Medicago sativa L.

Abstract: Ethylene biosynthesis during different phases of somatic embryogenesis in Medicago sativa L. cv. Rangelander using two regeneration protocols, RPI and RPII, was studied. The highest ethylene production was detected during callus growth on induction medium in both regeneration protocols. Significantly less ethylene was produced by embryogenic suspension than by callus (RPII). Developing embryos synthesized higher amounts of ethylene than mature embryos. Production of ethylene was strongly limited by the availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 33 publications
2
26
0
Order By: Relevance
“…An ACO was previously reported as up-regulated during SE, although transcript accumulation was higher on the abaxial side than the adaxial side that forms embryos (Thibaud-Nissen et al, 2003). In other systems, ethylene has been shown to have a role in cotyledon development of B. napus microspore embryos (Hays et al, 2000) and in the development and conversion of alfalfa somatic embryos (Kepczynska et al, 2009;Kepczynska and Zielinska, 2011). In some situations, a suppression of embryogenesis with ethylene is observed (for review, see Jiménez and Thomas, 2006), and a number of systems show enhanced SE by the addition of AgNO 3 to medium (for review, see Kumar et al, 2009).…”
Section: Stress Ethylene and Somatic Embryogenesismentioning
confidence: 91%
“…An ACO was previously reported as up-regulated during SE, although transcript accumulation was higher on the abaxial side than the adaxial side that forms embryos (Thibaud-Nissen et al, 2003). In other systems, ethylene has been shown to have a role in cotyledon development of B. napus microspore embryos (Hays et al, 2000) and in the development and conversion of alfalfa somatic embryos (Kepczynska et al, 2009;Kepczynska and Zielinska, 2011). In some situations, a suppression of embryogenesis with ethylene is observed (for review, see Jiménez and Thomas, 2006), and a number of systems show enhanced SE by the addition of AgNO 3 to medium (for review, see Kumar et al, 2009).…”
Section: Stress Ethylene and Somatic Embryogenesismentioning
confidence: 91%
“…When using a regeneration system in which two main phases of SE, induction and differentiation, are separated by an additional step of embryogenic tissue proliferation, we observed that ethylene production during callus growth, proliferation of cell suspension and embryo development in Medicago sativa L. cv. Rangelander are greatly altered during SE (Kępczyńska et al 2009a). Ethylene accumulation in vessels was correlated with the ability of tissues to produce ACC and to convert it into ethylene.…”
Section: Introductionmentioning
confidence: 99%
“…When investigating the phytohormonal regulation of somatic embryogenesis, E. Kępczyńska from Szczecin University evaluated the influence of gibberelins [113], ABA and MeJA [114,115], ethylene [116] and auxins on specific phases of SE (i.e. induction, proliferation, differentiation, maturation and embryo regeneration) in two model species: Medicago sativa and M. truncatula.…”
Section: Somatic Embryogenesismentioning
confidence: 99%
“…induction, proliferation, differentiation, maturation and embryo regeneration) in two model species: Medicago sativa and M. truncatula. She found that endogenous jasmonates and ABA (natural growth inhibitors) restrict proliferation and growth of proembryogenic callus but stimulate germination and conversion of alfalfa embryos [116]. She continues her work on increasing the rates of germination and conversion of embryos of cultivated plants, aiming to formulate the optimal conditions for somatic embryo production.…”
Section: Somatic Embryogenesismentioning
confidence: 99%